KOPERASI DALAM PERSPEKTIF SYARIAH ISLAM - Risqy Kurniawan, Rachmad Risqy Kurniawan (Cakrawala Akuntansi & Manajemen, 2024)
The phenomenon of the spread of cooperative practices which do not actually bring prosperity to society actually creates new problems in society because they are no different from mobile banks and online loans which, like loan sharks, suck the economic life out of the people. This research aims to explain the concept of cooperatives in accordance with Islamic sharia so that they bring prosperity and blessings to their members in particular and the people in general. The method used in this research is qualitative-descriptive with literature study which is then concluded using the Islamic law istinbath method. The results of this research state that sharia cooperatives that are based on Islamic sharia for all aspects must comply with sharia rules so that they are considered permissible/permissible and return to the cooperative's initial goal, namely prosperity.